Contesting carceral logic
1 online resource.
Keywords: "Contesting Carceral Logic provides an innovative and cutting-edge analysis of how carceral logic is embedded within contemporary society, emphasizing international perspectives, the harms and critiques of using carceral logic to respond to human wrongdoing, and exploring penal abolition thought. With chapters from scholars across many disciplines, people in prison, as well as penal abolition activists, the book explores what a future without carceral logic would look like, as well as how such a future is to be developed. The book is also an exploration of penal abolition thought as it is developing in the twenty first century. Diverse geographical, cultural, identity and experiential frames inform the book's themes of analysing carceral logic as it harms disparate people in disparate places, creating anti-carceral knowledge, exploring case studies pointing to radical alternatives, and to contesting carceral logic from below. Ultimately, Contesting Carceral Logic provides the reader with an alternative and critical perspective from which to reflect on carceral logic, the punitive state, and the criminalizing systems that almost exclusively dominate across the world. Finally, it raises the questions of how we are to build communities as well as transform our response to human wrongdoing in ways that are not defined by racism/ethnocentrism, class war, and heteropatriarchy. Contesting Carceral Logic will be of great interest to not only scholars and activists, but also provides an introduction to key carceral issues and debates for students of penology, criminology, social policy, geography, politics, philosophy, social work, and social history programs in countries all around the world"--